Modeling Atmospheric Transport of Cosmogenic Radionuclide 10Be Using GEOS‐Chem 14.1.1 and ECHAM6.3‐HAM2.3: Implications for Solar and Geomagnetic Reconstructions - Minjie Zheng; Florian Adolphi; Sylvaine Ferrachat; Florian Mekhaldi; Zhengyao Lu; Andreas Nilsson; Ulrike Lohmann (Geophysical Research Letters, 2024)
Abstract A prerequisite to applying 10Be in natural archives for solar and geomagnetic reconstructions is to know how 10Be deposition reflects atmospheric production changes. However, this relationship remains debated. To address this, we use two state‐of‐the‐art global models GEOS‐Chem and ECHAM6.3‐HAM2.3 with the latest beryllium production model. During solar modulation, both models suggest that 10Be deposition reacts proportionally to global production changes, with minor latitudinal deposition biases (<5%). During geomagnetic modulation, however, 10Be deposition changes are enhanced by ∼15% in the tropics and attenuated by 20%–35% in subtropical and polar regions compared to global production changes. Such changes are also hemispherically asymmetric, attributed to asymmetric production between hemispheres. For the solar proton event in 774/5 CE, 10Be shows a 15% higher deposition increase in polar regions than in tropics. This study highlights the importance of atmospheric mixing when comparing 10Be from different locations or to independent geomagnetic field records.